The Rhythms of NEP: The Fox Trot Calls the Time - Ginzburg, Lyubov (Journal of Russian American Studies, 2019)
The article revisits the story behind Dmitri Shostakovich's orchestration of a popular tune, "Tea for Two," by Vincent Youmans in 1924. The episode is discussed within a broader context of the NEP era and its infatuation with the innovative American art form known as jazz. Steeped with an array of newly revealed circumstances, it is bestowed with unexpected new meanings and symbols that reverberate in such disciplines as comparative cultural studies, international affairs, and Russian-American relations.